(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes the ways in which the meaning of respect is expressed in Jane Austen’s works, and how such moral values as respect and justice are presented in her novels. In Austen’s works, respect plays an important role not only in expressing personal relationships, but also in expressing interactions between society and social classes. The article highlights the aspects that distinguish respect and personal freedom among the characters in her works, by describing the difference between the ideal and real relationships expected by society. Jane Austen, through her works, critically evaluates the social structure of her time and shows the importance of appreciating respect and values.